Genetic Diversity among Mycobacterium bovis Isolates: a Preliminary Study of Strains from Animal and Human Sources - Sales, M. P. U. (American Society for Microbiology, 2001)
Mycobacterium bovis has the broadest host range of species in the Mycobacterium tuberculosis complex and is responsible for disease in humans and diverse animal species. We report on genotypic differences at multiple loci among 13 isolates derived from a range of human and animal infections. All isolates were classified as M. bovis by phenotypic analysis but could be subdivided into five distinct genotypes based on polymorphisms at the pncA and oxyR loci, the status of the RD5 deletion region, and the spoligotype pattern. These findings suggest the existence of a spectrum of strains with genotypic characteristics between those of M. tuberculosis and M. bovis.